Synthesis of glutamic-modified polyether copolymer as a novel non-phosphorous inhibitor for calcium carbonate scales in cooling water systems. Issue 41 (1st September 2016) - Wu, Zhen; Zhou, Yuming; Yao, Qingzhao; Wang, Huchuan; Liu, Yanmei; Tao, Weiting; Chu, Xueyuan; Sun, Wei; Wu, Wendao
Abstract: A novel non-phosphorous copolymer acrylic acid-allyloxy polyethoxy glutamate (AA-APEU) had been synthesized and developed as an efficient calcium carbonate scale inhibitor for cooling water systems. The structure of the new copolymer was characterized by Fourier transform infrared spectra and 1 H NMR. The inhibition property of the non-phosphorous copolymer toward CaCO3 in the artificial cooling water was studied through static scale inhibition tests. It was found that AA-APEU exhibited excellent ability to control calcium carbonate scale, with approximately 71.8% calcium carbonate inhibition at a level of 8 mg/L. The micromorphology and crystal of calcium particles were investigated with a combination of scanning electronic microscopy and X-ray powder diffraction analysis, respectively.